2013
DOI: 10.1089/jop.2012.0203
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Tumor Necrosis Factor-Alpha Inhibitors for Neovascular Age-Related Macular Degeneration Suboptimally Responsive to Antivascular Endothelial Growth Factor Agents: A Pilot Study from the Pan American Collaborative Retina Study Group

Abstract: Intravitreal infliximab and adalimumab do not appear to benefit eyes with CNV that responded suboptimally to anti-VEGF agents. Intravitreal injections of infliximab may elicit a severe intraocular inflammatory reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
(43 reference statements)
0
25
0
Order By: Relevance
“…Indeed, TNF has been considered a therapeutic target in exudative AMD. Although the inhibition of TNF-α leads to the reduction in CNV size and leakage in experimental models (13) , clinical research studies have shown inconsistent results (16,28) . It has also been demonstrated that TNF-α stimulates the production of IL-6 (16) , an important marker of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TNF has been considered a therapeutic target in exudative AMD. Although the inhibition of TNF-α leads to the reduction in CNV size and leakage in experimental models (13) , clinical research studies have shown inconsistent results (16,28) . It has also been demonstrated that TNF-α stimulates the production of IL-6 (16) , an important marker of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The Pan American Collaborative Retina Study Group has published the largest series on the use of intravitreal infliximab in both DME and exudative AMD. 1,36 The results have been clearly disappointing. Not only is intravitreal infliximab not effective in exudative AMD and DME but may also cause severe intraocular inflammation in a large percentage of patients.…”
Section: Replymentioning
confidence: 99%
“…However, repeated injections would be necessary to achieve prolonged therapeutic level of infliximab, which may lead to adverse effects and complications 16. In addition, high dose of intravitreal infliximab at the time of infusion may induce severe uveitis 17. To improve the efficacy and safety of intravitreal delivery, a controlled drug-release system is required that are biodegradable and can maintain the therapeutic concentration of drugs within the vitreous body.…”
Section: Introductionmentioning
confidence: 99%